Efficient Production of Specialized Polymers with Highly Flexible Small‐Scale Plants. Issue 6 (23rd March 2021) - Bruns, Bastian; Becker, Tristan; Riese, Julia; Lier, Stefan; Werners, Brigitte
Abstract: Shortened product life cycles and increased demand for specialized products lead to more challenges in efficiently satisfying customer needs. Customer demands are increasingly uncertain in terms of type, location, and volume. As a result, more flexible chemical production plants are required. Modular small‐scale plants can be installed in transportation containers and, therefore, offer the flexibility of easy relocation, enabling production close to the customer or supplier. In a mathematical optimization model, the economic benefit of small‐scale plants in the specialty chemicals market of polymer production is analyzed. Different scenarios created from the real data of a chemical company show that the use of small‐scale plants may lead to a significant reduction in total costs that is mainly due to the transportation costs of raw materials and products. Abstract : The opportunities of small‐scale production plants for a real‐world scenario are examined. The benefits of modular small‐scale plants for the production of specialized polymers are demonstrated. A mathematical optimization program is applied to analyze eight scenarios which were created from real data. The flexibility of small‐scale plants significantly reduces costs for the given scenario.